2018
DOI: 10.1016/j.mri.2017.09.004
|View full text |Cite
|
Sign up to set email alerts
|

Test-retest reliability of cerebral blood flow in healthy individuals using arterial spin labeling: Findings from the EMBARC study

Abstract: Introduction Previous investigations of test-retest reliability of cerebral blood flow (CBF) at rest measured with pseudo-continuous Arterial Spin Labeling (pCASL) demonstrated good reliability, but are limited by the use of similar scanner platforms. In the present study we examined test-retest reliability of CBF in regions implicated in emotion and the default mode network. Material and methods We measured absolute and relative CBF at rest in thirty-one healthy subjects in two scan sessions, one week apart… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
28
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
4
2
1

Relationship

1
6

Authors

Journals

citations
Cited by 28 publications
(34 citation statements)
references
References 60 publications
6
28
0
Order By: Relevance
“…Generally, pCASL parameters consisted of a 1516 ms labelling duration, 1500 ms post-labelling delay, 4460 ms/17 ms TR/TE, 3.44 × 3.44 × 5 mm [3] in-plane resolution, multi-slice acquisition in ascending order, 29 slices covering the whole brain, 35 pairs, 220 × 220 mm FOV, 64 × 64 matrix, 90° excitation flip angle, with scan duration of approximately 5 min. For further details on the pCASL sequence, refer to Almeida et al [9]. These imaging parameters are comparable and consistent with recommendations from a recent consensus paper [7].…”
Section: Methodssupporting
confidence: 81%
See 1 more Smart Citation
“…Generally, pCASL parameters consisted of a 1516 ms labelling duration, 1500 ms post-labelling delay, 4460 ms/17 ms TR/TE, 3.44 × 3.44 × 5 mm [3] in-plane resolution, multi-slice acquisition in ascending order, 29 slices covering the whole brain, 35 pairs, 220 × 220 mm FOV, 64 × 64 matrix, 90° excitation flip angle, with scan duration of approximately 5 min. For further details on the pCASL sequence, refer to Almeida et al [9]. These imaging parameters are comparable and consistent with recommendations from a recent consensus paper [7].…”
Section: Methodssupporting
confidence: 81%
“…In recent work, both reliability of cerebral blood perfusion and its potential as a disease-state marker have been investigated. Perfusion has been observed to be reliable in healthy controls across time and in detecting abnormalities in MDD participants as compared to healthy controls [8], [9]. Differences in perfusion have been identified between MDD participants and healthy controls in some but not all studies [10], [11], [12], [13].…”
Section: Introductionmentioning
confidence: 98%
“…In accordance with previous studies ( Chen et al, 2011 ; Jain et al, 2012 ; Jahng et al, 2005 ; Hodkinson et al, 2013 ; Zou et al, 2015a ; Almeida et al, 2018 ), our results demonstrated excellent retest reliability of both mean and regional CBF for all the four resting conditions. Among the 4 resting conditions, FIX presented the lowest retest reliability, while EC yielded higher (but not significantly) reliability and reproducibility than EO and PVT.…”
Section: Discussionsupporting
confidence: 92%
“…Brain perfusion was imaged using a pseudo continuous arterial spin labeling (pCASL) sequence (Wu et al 2007), which has been shown to have good to excellent scan-rescan reliability within site (Almeida et al 2018). The sequence used a single-shot spin-echo EPI readout.…”
Section: Perfusion (Asl) Measures Of Cerebral Blood Flow (Cbf)mentioning
confidence: 99%